Oversharing: Urgensi Privasi di Era Digital - Alpiah, Siti; Asbari, Masduki; Saputri, Indah Ayu; Adilya, Nur Rahma (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to find out the causes of oversharing by viralizing privacy details to get attention. This study report uses a descriptive qualitative method by doing simak catat because the source of data obtained by listening to oral narratives from the Youtube channel Satu Persen - Indonesian Life School entitled "Oversharing: Selling Privacy for Attention. One Insight Episode 17" presented by him. The results of this study explain that learning about oversharing in the context of selling privacy for attention is to provide an understanding of the potential risks and consequences of such behavior. Learning about oversharing and selling privacy for attention is important, especially in an ever-evolving digital world, where personal information can be disseminated quickly. The goal is to help individuals protect themselves and take wiser action in sharing personal information online.